Flipped classroom in Pediatrics: undergraduate Medicine students perception during the Covid-19 pandemic (European Journal of Health Research, 2021)
Flipped classroom is an innovative teaching and learning methodology, that has demonstrated being effective in the health area. In the context of the actual confinement due to the Covid-19 Pandemic, it perfectly adapts to the new reality of medical teachers and students, as it substitutes face – to – face learning for online tutorials and telepresence meetings.The present study describes the medicine undergraduate student’s perception, in the Pediatrics course, with respect to inverted classroom classes performed during the COVID-19 Pandemic between June and November 2020. This study involved 93.3% of students enrolled in the university's paediatrics course, the sample consisted of 70 students, with an average age of 22, of whom 30% were men and 70% women, all respondent to the Flipped Classroom Perception Instrument survey. The results showed above 70 % positive perception on all the aspects that were evaluated among them.A positive perception of the inverted classroom is evidenced by the medical students who took the pediatrics course. It is suggested to perform another after study, to evaluate if this methodology impacts the academic results, compared with traditional learning methodologies.
Keywords: flipped classroom; education; medical education; coronavirus; pandemic